Influence of disease duration and socioeconomic factors on the prevalence of infection and hospitalization in rheumatoid arthritis: KRAC study. (11th April 2019) - Chandrashekara, S.; Shobha, Vineeta; Dharmanand, Balebail G.; Jois, Ramesh; Kumar, Sharath; Mahendranath, Kurugodu Mathada; Haridas, Vikram; Prasad, Shiva; Singh, Yogesh; Daware, Manisha Ashwin; Swamy, Anupama; Subramanian, Ramaswamy; et al.
Abstract: Aim: The use of healthcare resources by rheumatoid arthritis (RA) patients can be related to the presence of disease, comorbid conditions, use of steroids, and the combined use of immunosuppressants. This study evaluated the risk factors associated with infection and hospitalization in RA. Methods: This multicenter, cross‐sectional study enrolled 3247 RA subjects fulfilling the 2010 American College of Rheumatology/European League Against Rheumatism criteria to examine the prevalence of hospitalization and episodes of documentable non‐tubercular infections as a part of the "Karnataka rheumatoid arthritis comorbidity" study (KRAC). The study included 2081 subjects and 1166 were excluded due to incomplete data. Demographic, clinical and treatment variables were collected, and the events related to infections and hospitalization were extracted from the medical records. Comparative analysis and multivariate logistic regression were performed. Results: Around 22% of the subjects had hospitalizations and 2.9% had infections. Infections were pertaining to dental (1.3%), urinary tract (1.6%) and candidiasis (0.2%). Skin‐ and soft tissue‐related infections were found in 1.8% and 0.3% of patients, respectively. Increased need of hospitalization in RA patients was associated with advanced age (≥60 years), lower education, family income, and longer duration of RA. Presence of comorbidity, usage of three or more disease‐modifying anti‐rheumatic drugs (DMARDs) and family income influenced the likelihood of infection. Dental infections were less likely in working subjects and more likely in patients with increased disease duration, higher family income, comorbidities and those between the age group 40‐59 years. Urinary tract infection was associated with DMARD usage. Conclusion: Patient‐specific risk factors should be considered to improve treatment strategies and to reduce the risk of infection and hospitalization in RA patients.